Creating employees’ motivational paths in the retail trade - Teuvo Kantanen (Taylor & Francis Group, 2017)
This study examines the manifestation of intrinsic motivation by exploring the sources of intrinsic and extrinsic motivation among employees of a retail hypermarket. The research uses narrative and ethnographical analysis from 24 interviews. Two unique dimensions were created for motivational power—source and growth process—for a new typology of work motivation. The typology consists of four processes: intrinsic regulation, intrinsic valuation, extrinsic valuation, and extrinsic regulation. The results show how intrinsic motivation can be reinforced through these processes. Recommendations are presented for different personnel teams in the service sector.